POTENSI EKSTRAK ETANOL 50% TERPURIFIKASI BIJI PINANG (Areca Catechu L.) SEBAGAI PENYEMBUH LUKA BAKAR - Egi Ramadhan Sm; Humaryanto; Fathnur Sani Kasmadi; Wahyu Indah Aurora; Hanina (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2025)
Burns require effective therapy to accelerate healing and prevent complications. Areca nut (Areca catechu L.) extract contains secondary metabolite compounds that have wound healing activities, namely anti-inflammatory and antioxidant. The purpose of this study was to analyze the potential of the purification process of 50% ethanol extract of areca nut (Areca catechu L.) on the potential for wound healing in test animals. The method used in this study was an experimental method. The mice used in each group consisted of 5 mice, namely a negative control (vaselin flavum), a positive control (Bioplacenton®), and three treatment groups of areca nut extract of 2%, 4%, and 6% mixed with vaselin flavum ad 100%. Second-degree burns were treated topically every day for 21 days, with wound diameter measurements every three days and histopathological analysis on the 22nd day. The 6% extract gave the best results, with wound healing of 51.58%. Histopathology showed better epidermal regeneration, collagen formation, vascularization, and decreased inflammation in the treatment group. The results of the study showed that a 50% purified ethanol extract of areca nut seeds has potential as a burn healing agent. Statistically, a 6% extract was the best for burn healing (P<0.05).